A new subspecies of the squirrel Sciurus variegatoides Ogilby from Costa Rica - McPherson, A. B. (1971)
The addition of S. v. loweryi and S. v. melania to the squirrel fauna of Costa Rica clarifies the distributional hiatus which existed previously. Sciurus v. loweryi is a new subspecies from the Valle de Coto Brus and the Valle del General. It is a very distinctive tawny squirrel with a black dorsal stripe. Sciurus v. melania is now known from as far north as Parrita. It is an inhabitant of the Pacific coastal lowlands. Near the Río Grande de Tárcoles, S. v. melania intergrades with S. v. rigidus.